Study of pressure sensors placement using an abdominal aortic aneurysm (AAA) Model - L. A. Rocha (2010)
An Abdominal Aortic Aneurysm (AAA) model for post-EVAR (endovascular aneurysm repair) analysis, including the blood flow, the bifurcated stent-graft, the aorta aneurysm wall motion and the stagnant blood inside the aneurysm sac, was built and solved using a Fluid Structure Interaction (FSI) code. The post-EVAR analysis aims to check the feasibility of EVAR surveillance using a remote pressure sensor, and the study of the pressure variations inside the aneurysm sac to determine the best placement position for the pressure sensor(s). First results suggest that aneurysm sac pressure measurement is feasible and can be a good indicator of aneurysms post-EVAR evolution.